Issues of legal regulation of tourism and recreational activities in specially protected natural areas - Yu. A. Pshenichnykh; Yu. V. Morozova (Вестник университета)
Specially protected natural areas are unique sites that attract a significant number of tourists due to their natural beauty and ecological value. The issues of legal regulation of tourism in such areas is becoming critical to ensure a balance between natural ecosystems preservation and tourism infrastructure expansion. A comprehensive study of legal aspects makes it possible to identify ways to improve legislation and eliminate administrative barriers, which is necessary for the sector’s sustainable development. The issue is of paramount importance in the context of modern challenges related to environmental safety and the need to actively attract investment in the tourism industry. Legal regulation of tourism and recreational activities in specially protected natural areas in Russia has been analyzed. The issues of legislation instability and administrative barriers affecting the domestic tourism industry development, especially in the context of restrictions on outbound tourism, have been studied. The changes in the legislation on protected areas, which came into force in 2023, and their impact on ecological tourism development have been considered. The conflict of interests between the environmental community and business in the context of new legal norms implementation, as well as intractable issues of interpretation of the “tourist routes” and “trails” concepts, their categorization, and the need to be accompanied by guides have been analyzed. Recommendations on improving the conceptual apparatus and developing bylaws to eliminate legal uncertainty have been given. Law enforcement and organizational issues arising in recreational facilities construction wit hin the boundaries of specially protected natural areas have been studied, and ways to solve them have been proposed.